DISCRIMINATORY RESTRICTIONS TO OBTAIN THE STATUS OF RESIDENT OF THE LEGAL REGIME ACTION CITY - Tarasiuk, Serhii (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2022)
Purpose: to study the basic principles based on freedom of enterprise and guarantees of competition protection in the conditions of launch of the legal regime of the legal regime Diia City, namely the peculiarities of the residence of the legal regime Diia City in the context of ensuring the right to freedom of business and prohibiting restrictions on competition. Methods of research: general and special legal methods, including analysis, system functional method and formal juridical method. Results: generalized basic conditions for acquiring the status of a resident of Diia City and confirming compliance with such criteria. Discussion: the Constitution provides for the right to freedom of entrepreneurial activity, which is not prohibited by law, and a prohibition on restricting competition. Entrepreneurs must be provided with equal access to the state-guaranteed legal regime Diia City. The current legal regime of Diia City in order to ensure equal access to it for business entities is subject to study. The main criteria for obtaining the status of resident of the legal regime Diia City are the implementation of economic activities in the digital economy, the list of which is determined by law, the requirements for the share of income from such activities and requirements for attracting labor resources, number of employees. However, there is a mitigation exception for certain categories of entities. The introduction of special conditions for economic activity for a particular sector of the economy is always of particular interest to the legal community and business. Scholars are interested in this topic both in terms of studying new legal constructions, especially in the context of legal conflicts pointed out by lawyers. It is important for business to understand the correct application of the benefits and guarantees provided by law with strict observance of the constitutional principles of freedom of entrepreneurial activity and the prohibition to restrict competition. To some extent, this study aims to address the criticism of some businesses about the «digital collective farm» and unequal conditions for competition.